2000
DOI: 10.1080/713683039
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial predictors of smoking and exercise during pregnancy

Abstract: This study examined health behaviours among nulliparous pregnant Swedish women. Structural equation modelling (N 5 350) was used to predict smoking and exercise at gestational weeks 20 and 32 from psychosocial factors measured in early and mid-pregnancy. Although women altered their lifestyle early in pregnancy, so that by gestational week 20 both smoking and exercise had declined, previous behaviours remained strong and consistent predictors of later behaviours. Hostility and health awareness predicted smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 61 publications
4
46
0
Order By: Relevance
“…Smoking during pregnancy cooccurs with numerous potential confounding variables that are related to childhood outcomes, including maternal psychiatric symptoms of hostility, depression (Anda et al, 1990;Fergusson, Goodwin, & Horwood, 2003;Rodriguez, Bohlin, & Lindmark, 2000;Schuetze & Eiden, 2006;Whiteman, Fowkes, Deary, & Lee, 1997), and anxiety (Parton et al, 1998), and Attention-Deficit Hyperactivity Disorder (ADHD) (Flick et al, 2006;Goodwin, Keyes, & Simuro, 2007;Kodl Middlecamp & Wakschlag, 2004). Pregnant smokers are also more likely to be young, poor, unmarried, and engage in other risky health behaviors during pregnancy, including alcohol and other drug use, and have suboptimal nutrition (Baghurst, Tong, Woodward, & McMichael, 1992;Breslau, 1995;Dani & Harris, 2005;Pickett, Wilkinson, & Wakschlag, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Smoking during pregnancy cooccurs with numerous potential confounding variables that are related to childhood outcomes, including maternal psychiatric symptoms of hostility, depression (Anda et al, 1990;Fergusson, Goodwin, & Horwood, 2003;Rodriguez, Bohlin, & Lindmark, 2000;Schuetze & Eiden, 2006;Whiteman, Fowkes, Deary, & Lee, 1997), and anxiety (Parton et al, 1998), and Attention-Deficit Hyperactivity Disorder (ADHD) (Flick et al, 2006;Goodwin, Keyes, & Simuro, 2007;Kodl Middlecamp & Wakschlag, 2004). Pregnant smokers are also more likely to be young, poor, unmarried, and engage in other risky health behaviors during pregnancy, including alcohol and other drug use, and have suboptimal nutrition (Baghurst, Tong, Woodward, & McMichael, 1992;Breslau, 1995;Dani & Harris, 2005;Pickett, Wilkinson, & Wakschlag, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Trait hostility consistently predicts higher smoking rates in both men and women (e.g., Lipkus, Barefoot, Williams & Siegler, 1994;Siegler, Person, Barefoot & Williams, 1992;Whiteman, Fowkes, Deary, & Lee, 1997). In addition, one recent study found that hostility during the first trimester predicted smoking during the second and third trimesters (Rodriquez, Bohlin & Lindmark, 2000).…”
Section: Nih Public Accessmentioning
confidence: 99%
“…Trait hostility consistently predicts higher smoking rates in both men and women (e.g., Lipkus, Barefoot, Williams & Siegler, 1994;Siegler, Person, Barefoot & Williams, 1992;Whiteman, Fowkes, Deary, & Lee, 1997). In addition, one recent study found that hostility during the first trimester predicted smoking during the second and third trimesters (Rodriquez, Bohlin & Lindmark, 2000).The importance of considering negative affect of pregnant smokers is underscored by the rapidly increasing body of literature that shows a range of nonoptimal developmental outcomes among the infants and children of women with increased levels of depression and hostility. Independent of cigarette smoking, parents who exhibit higher levels of depression are less sensitive caregivers, more likely to display flatter affect during mother-child interactions and to provide less stimulation to their infants (Cohn & Campbell, 1992;del Carmen, Pederson, Huffman, & Bryan, 1993;Field, 1992;Howard et al, 1995;Jameson, Gelfand, Kuczar, & Teti, 1997;Weinberg & Tronick, 1998).…”
mentioning
confidence: 92%
“…The emphasis was on brisk walking, which is popular among pregnant smokers. 62 As a further option, a home-based antenatal exercise digital versatile disc (DVD) and booklet were provided. In addition, participants were given a pedometer for monitoring their daily steps (Digi-Walker SW-200; Great Performance Ltd, London, UK).…”
Section: Methodsmentioning
confidence: 99%